Rancang Bangun Prototype Pembangkit Listrik Tenaga Mikro Hidro (PLTMH) Dengan Studi Kasus Saluran Irigasi Di Desa Medewi Kecamatan Pekutatan Kabupaten Jembrana - Irene Trivania; Tom Gerraldo Salomo Situmeang; Martin Luhut Ariberthson Sihaloho; Anak Agung Ngurah Amrita; Lie Jasa; I Wayan Sukerayasa; Pratolo Rahardjo; Dewa Ayu Sri Santiari (Majalah Ilmiah Teknologi Elektro, 2025)
Micro Hydro Power (MHP) is a small power plant that uses water to generate electricity. It can be found in irrigation canals, rivers, or waterfalls. The amount of water and head height are important factors in determining the power output. The irrigation canal in Medewi Village is being used as a research location for MHP. Researchers will use the data to perform calculations and design a prototype. They will also conduct an economic analysis of the MHP to determine its feasibility. The discharge at the research location is 0.23 m3/s, and the waterfall is 2.24 m high. Through the calculation results, the researchers determined that the turbine is a crossflow turbine. The turbine power is 3.9 kW, the generator power is 4.375 kVA, and the turbine power in the homer software is 4.195 kW. The cost of building the MHP in the irrigation canals in Medewi Village is IDR20.391.899,26. With a 6% discount rate, the BCR is 1,51, the NPV value is IDR30.827.069, the IRR is 12,3%, and the BEP result per unit The payback period is 1 year 5 months and 2 weeks. Selling 46.585,056 kWh results in an LCC of IDR44.598.314. Using MHP throughout its economic life results in a cost that is less than the price paid to PLN.